Penggunaan dan Ketepatan Konjungsi dalam Teks Deskripsi dan Teks Fantasi oleh Siswa SMP - Pebria, Cica Dwi; Rasyid, Yulianti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study aims to describe the use and accuracy of conjunctions in descriptive texts and fantasy stories written by seventh-grade junior high school students. The study used a descriptive qualitative approach with data in the form of conjunctions in 30 descriptive texts and 30 fantasy texts obtained through writing assignments, which were then analyzed through identification, classification of types, and accuracy assessment based on Chaer and KBBI criteria. The results show that descriptive texts contain 159 conjunctions with 100 correct uses and 59 incorrect uses, while fantasy texts contain 202 conjunctions with 150 correct uses and 52 incorrect uses. Both types of texts were dominated by coordinative conjunctions, especially “and,” but fantasy texts showed greater variation in temporal conjunctions and sequence of events, resulting in a more coherent flow. These findings confirm that genre characteristics influence the choice and function of conjunctions, while also indicating the need to strengthen text-based conjunction learning in descriptive and fantasy text writing in junior high school.